Perlindungan Konsumen Terhadap Pembelian Sepeda Motor Baru Mengenai Kerusakan Rangka Esaf Ditinjau Dari Perspektif Ibnu Taimiyah dan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Nila Rahmawati Lubis; Fatimah Zahara (UNES Law Review, 2023)
Motorcycle vehicles at this time are one of the primary vehicles used by the majority of people in daily activities. So that a motorcycle vehicle that is safe and suitable for use is a great hope of the community, especially in the frame which is the most important part of a vehicle. Lately cases that are rife in the community are damage to the eSAF frame resulting in broken and porous Honda brand vehicles, several incidents of broken motorcycles in the middle of the road, this is what attracts the author's attention to examine more deeply about what causes it and how Ibn Taymiyah's perspective and the Consumer Protection Law on this problem. This research is qualitative research with an empirical normative approach method using a type of research approach, namely library research. The results of this study show that there are rampant cases of damage to Honda motorcycle frames because they use eSAF type frames that are not good from previous types of frames, while from AHM explained that every product they market has been checked and is suitable for use. According to Ibn Taymiyyah in the principle of buying and selling is not justified this practice, because the frame is in the vehicle and not visible, there should be liability for damage suffered by consumers. And in terms of consumer protection, precisely in article 7 letters a-g has not been effectively applied in this broken frame problem